STRATEGI INOVASI PENINGKATAN KINERJA BANK PERKREDITAN RAKYAT DI JAWA BARAT - Ucu Supriatna, - (2023)
ABSTRACT The banking sector has undergone a rapid transformation due to the rapid development of technology which has created increasingly fierce competition. Rural Banks (BPR) must immediately accelerate changes to survive with the much greater competitiveness of commercial banks and the emergence of non-bank financial institutions such as financial technology (fintech). This research was conducted to encourage BPR performance improvement in a situation of increasingly fierce competition, so this study aims to examine the effect of implementing BPR innovation and partnership program in creating better business performance. Using a sample of 72 BPRs in West Java Province, they were analyzed using Structural Equation Modeling. First, scanning the external and internal environment is carried out, then this study selects a Technology-Based Product Strategy, Technology-Based Service Strategy, and Technology-Based Network Strategy which represent the dimensions of innovation strategy. Meanwhile, the partnership program is represented by the Marketing Partnership, Financial Partnership, Distribution Partnership, Supply Chain Partnership, and Technology Partnership. The research results show that the identification of the external and internal environment influences the implementation of the innovation strategy and its implementation in the form of a partnership program. This innovation strategy has an impact on Business Performance. The innovation strategy with technology-based products is the most important variable because it has the greatest influence. Likewise, the implementation of the partnership program has a significant effect on business performance, and the marketing partnership program has the greatest influence. In the end, how successfully a new technology-based product is launched is the most attractive way to attract customers so that BPR performance targets can be achieved properly. Keywords: BPR, innovation, partnership, bank performance